KAJIAN SEMIOTIKA ROLAND BARTHES DALAM PUISI: SAJAK MATAHARI DAN SAJAK BURUNG-BURUNG KONDOR KARYA W.S RENDRA - Qusayri, Muhammad; Sosrohadi, Somadi; Sukirno, Sukirno (Universitas Negeri Makassar, 2024)
The representation of the meaning of human value relationships in W.S. Rendra's Sun Rhymes and Condor Birds poems is the main objective of the research. This research is descriptive and qualitative. The data used in the research was sourced from poems by W.S. Rendra that have the titles Sun rhyme and Concert Bird rd Rhyme.